Keputusan Indonesia Mengeluarkan Kebijakan Pelarangan Ekspor Bijih Nikel pada Tahun 2019 - Janwal Almuthazim; Apriwan; Cory, Silvi (Hubungan Internasional Universitas Andalas, 2025)
In 2019, through the Minister of Energy and Mineral Resources Regulation Number 11/2019, the Indonesian government officially issued a policy to ban the export of nickel ore. The policy received negative reactions from both domestic and international actors, as it was considered disadvantageous to Indonesia's interests and contrary to international trade rules in the World Trade Organization (WTO). This study examines whether the nickel ore export ban policy implemented by the Indonesian government is rational. out this, Graham T. Allison's Rational Actor Model theory is used, which consists of four stages, namely, determining goals and objectives, determining alternative policy options, determining the consequences of each policy option and the last is a rational choice. This research is categorized as qualitative research with a descriptive analysis approach, utilizing secondary data. Based on the results of the analysis, it is found that the nickel ore export ban policy issued in 2019 is not a rational choice because when viewed from the political, environmental, and economic aspects of the policy it produces more losses for Indonesia than benefits. The benefits gained are more likely to be enjoyed by multinational companies (MNCs) from China that have long invested in Indonesia. Keywords: Nickel Ore Export Ban Policy, Indonesia, China, Rational Actor Model, Multinational Corporation